Study of regularities of changes in the temperature near the U-shaped ground heat exchangers - Shuyushbayeva, N.N.; Kussaiynov, K.; Stoev, M.; Shaimerdenova, K.M.; Ospanova, D.A.; Akhmadiev, B.A.; Sadenova, K.K. (Ye.A.Buketov Karaganda State University Publishing house, 2015)
The article considers the results of a study heat transfer process is in ground heat exchangers, used for geothermal heat pumps. At the research facility performed experiments and calculations, confirming about the best of thermophysical indicators of moistened of sand. The experimentally determined the temperature distribution regularities in a neighborhood U-shaped of underground heat exchangers.
U-тəрізді жер асты жылуалмастырғыштары маңындағы температураның өзгерісін зерттеу
Исследование изменения температуры в окрестности U-образного грунтового теплообменника
Keywords: renewable energy; heat pumps; underground heat exchangers; the temperature distribution